2019
DOI: 10.3389/fncel.2019.00525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Inflammatory Cytokines From M1-Type Microglia/Macrophages at the Injured Site and Lumbar Enlargement With Neuropathic Pain After Spinal Cord Injury in the CCL21 Knockout (plt) Mouse

Abstract: Spinal cord injury (SCI) causes loss of normal sensation and often leads to debilitating neuropathic pain (NeP). Chronic NeP develops at or below the SCI lesion in as many as 80% of patients with SCI and may be induced by modulators of neuronal excitability released from activated microglia and macrophages. In the inflammatory response after SCI, different microglia/macrophage populations that are classically activated (M1 phenotype) or alternatively activated (M2 phenotype) have become of great interest. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…In spinal cord injury model of neuropathic pain, CCL21 depletion resulted in less M1‐type microglia/macrophages cell numbers, decreased M1‐type proinflammatory cytokines (e.g., TNF‐α and IFN‐γ) and attenuated pain hypersensitivity from day 14 after injury. In contrast to the peripheral nerve injury model, in which primary sensory neurons‐derived CCL21 are required for early microglia proliferation and pain initiation, CCL21‐knockout mice produced pain‐like responses similar to wide‐type mice at the early stage of injury (e.g., day 4) 93 . These findings indicated that CCL21 was dispensable for initiation of pain hypersensitivity but contributed to chronic pain maintenance in this model.…”
Section: Microglia‐neuron Interactions For Ongoing Chronic Pain Maintmentioning
confidence: 71%
“…In spinal cord injury model of neuropathic pain, CCL21 depletion resulted in less M1‐type microglia/macrophages cell numbers, decreased M1‐type proinflammatory cytokines (e.g., TNF‐α and IFN‐γ) and attenuated pain hypersensitivity from day 14 after injury. In contrast to the peripheral nerve injury model, in which primary sensory neurons‐derived CCL21 are required for early microglia proliferation and pain initiation, CCL21‐knockout mice produced pain‐like responses similar to wide‐type mice at the early stage of injury (e.g., day 4) 93 . These findings indicated that CCL21 was dispensable for initiation of pain hypersensitivity but contributed to chronic pain maintenance in this model.…”
Section: Microglia‐neuron Interactions For Ongoing Chronic Pain Maintmentioning
confidence: 71%
“…CCL21 is an effective microglia-activating chemokine, and its role in SCI has recently been reported. Research by Honjoh and his colleagues showed that compared with wild-type mice, the number of classically activated (M1 phenotype) microglia in mice with low expression of CCL21 gene mutations in the SCI model was significantly reduced [ 27 ]. This study suggests that CCL21 may be an important target for intervention in neuroinflammation after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gas6 has previously been shown to have a suppressive effect on TLR-mediated pro-inflammatory cytokine production in cardiomyocytes (Grommes et al, 2008), microglial cell lines (Li et al, 2019), mouse macrophages (Deng et al, 2011) and primary murine microglia (Binder et al, 2008). There is growing evidence linking alleviation of inflammation to morphological alterations in microglia which are associated with pro-inflammatory signaling responses and cytokine expression (Zhang et al, 2014(Zhang et al, , 2019Kalakh and Mouihate, 2017;Honjoh et al, 2019). This study used WT microglia to observe the potential modulatory effects of Gas6 on microglial morphological characteristics.…”
Section: Gas6mentioning
confidence: 99%